2018
DOI: 10.1200/jco.2018.78.3050
|View full text |Cite
|
Sign up to set email alerts
|

Intensifying Treatment of Childhood B-Lymphoblastic Leukemia With IKZF1 Deletion Reduces Relapse and Improves Overall Survival: Results of Malaysia-Singapore ALL 2010 Study

Abstract: Purpose Although IKZF1 deletion ( IKZF1) confers a higher risk of relapse in childhood B-cell acute lymphoblastic leukemia (B-ALL), it is uncertain whether treatment intensification will reverse this risk and improve outcomes. The Malaysia-Singapore ALL 2010 study (MS2010) prospectively upgraded the risk assignment of patients with IKZF1 to the next highest level and added imatinib to the treatment of all patients with BCR- ABL1 fusion. Patients and Methods In total, 823 patients with B-ALL treated in the Maly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 23 publications
2
72
0
Order By: Relevance
“…Deletions or mutations of IKZF1, encoding the IKAROS transcription factor, are associated with poor prognosis in some subtypes of B-cell precursor acute lymphoblastic leukaemia (BCP-ALL) (Mullighan et al, 2009;Clappier et al, 2015). IKZF1 status is therefore important for risk stratification and defining therapies (Stanulla et al, 2018;Yeoh et al, 2018). Most IKZF1 abnormalities are intragenic deletions, or deletions of the entire locus (Mullighan et al, 2008;Iacobucci et al, 2009;Marke et al, 2018), which lead to loss of IKAROS expression and/or function.…”
Section: Supporting Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Deletions or mutations of IKZF1, encoding the IKAROS transcription factor, are associated with poor prognosis in some subtypes of B-cell precursor acute lymphoblastic leukaemia (BCP-ALL) (Mullighan et al, 2009;Clappier et al, 2015). IKZF1 status is therefore important for risk stratification and defining therapies (Stanulla et al, 2018;Yeoh et al, 2018). Most IKZF1 abnormalities are intragenic deletions, or deletions of the entire locus (Mullighan et al, 2008;Iacobucci et al, 2009;Marke et al, 2018), which lead to loss of IKAROS expression and/or function.…”
Section: Supporting Informationmentioning
confidence: 99%
“…Our study, however, aimed at characterizing exon 1 deletions in molecular terms, and our cohort was too small and heterogeneous (Table SI) to correlate with clinical outcome. Nonetheless, since the 5 0 deletions are null alleles, like Dex2-8 and entire IKZF1 deletions, we suggest that they be considered as such during risk stratification (Yeoh et al, 2018). † Present address: Institut Paoli-Calmettes, Marseille, France.…”
Section: Supporting Informationmentioning
confidence: 99%
“…In particular, studies examining the prognostic impact of the IK6-generating intragenic deletion of exons 4-7 have been conflicting. [17][18][19][33][34][35][36][37] Further, in addition to inhibition of residual wild-type IKAROS, the IK6 isoform also heterodimerizes with other IKAROS family proteins such as HELIOS (encoded by IKZF2) and AIOLOS (encoded by IKZF3), inhibiting their function. Therefore, the transcriptomic and phenotypic impact of IK6 could differ from deletion of the entire IKZF1 gene.…”
Section: Gfp-tagged Ik6 Knock-in To the Endogenous Locus Mimics The Imentioning
confidence: 99%
“…16 While IKZF1 mutations and deletions are clinically correlated with poor outcome and increased risk of relapse, indicating IKZF1 status could be a useful prognostic marker, clinical trials to modulate therapeutic intensity based on IKZF1 status have had mixed results. [17][18][19] How the broad spectrum of IKZF1 genetic variants seen in B-ALL affect chemosensitivity and outcome and whether IKZF1 status is a relevant prognostic criterion only in the context of certain driver translocations/mutations remain unclear. 20 Some previously published in vitro studies using RNAi-mediated knockdown of IKZF1 have shown evidence of resistance to corticosteroids, 11,21 but others report no change in chemosensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Our study, however, aimed at characterizing exon 1 deletions in molecular terms, and our cohort was too small and heterogeneous (Table SI) to correlate with clinical outcome. Nonetheless, since the 5′ deletions are null alleles, like Δex2‐8 and entire IKZF1 deletions, we suggest that they be considered as such during risk stratification (Yeoh et al , ).…”
mentioning
confidence: 92%